Frequency of peripheral diseases in Korean patients with ankylosing spondylitis and the effectiveness of adalimumab. (29th July 2020) - Lee, Sang‐Hoon; Park, Won; Won Lee, Sung; Kim, Hyun Ah; Choe, Jung‐Yoon; Lee, Sang‐Heon; Lee, Shin‐Seok; Park, Sung‐Hwan; Park, Min‐Chan; Sheen, Dong‐Hyuk; Lee, Hye Soon; Lee, Yeon‐Ah; et al.
Abstract: Aim: Peripheral features contribute to disease burden in ankylosing spondylitis (AS). This study investigated the frequency of peripheral disease and effectiveness of adalimumab among Korean patients with AS. Methods: Peripheral disease was evaluated in consecutively enrolled patients with active AS (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] score ≥ 4). An adult subpopulation was subsequently enrolled in a prospective, observational study and received adalimumab 40 mg, every 2 weeks. During a 52‐week follow‐up, AS disease activity was assessed by BASDAI score, and effectiveness in peripheral disease assessed via changes in Maastricht Ankylosing Spondylitis Enthesitis Score (MASES; 0‐13), swollen joint and tender joint counts (SJC, 0‐44; TJC, 0‐46), and dactylitic digits from baseline. Results: Of 1161 Korean patients with AS, 178 (15.3%) and 306 (26.4%) had enthesitis and peripheral arthritis, respectively; dactylitis was diagnosed in 28 patients (2.4%). Of 201 patients enrolled in the observational study, 46.3%, 33.3%, and 3.0% had enthesitis, peripheral arthritis, and dactylitis, respectively. Overall, 75.1% of patients achieved >50% improvement in BASDAI score by week 12. Mean MASES was significantly reduced from 2.67 at baseline to 0.85 and 0.34 at weeks 12 and 52, respectively ( P  < .0001). Similarly, SJC and TJC improved significantly from 2.58 and 3.49 at baseline to 0.80 and 1.68, respectively, by week 12 ( P  < .0001). Dactylitis was resolved in all affected patients by week 28. Conclusion: Of these Korean patients with AS, those who received adalimumab demonstrated higher prevalence for peripheral symptoms and, subsequently, adalimumab treatment improved peripheral features of their AS.